ANALISIS PERUBAHAN SUHU DAN TEKANAN UDARA PERMUKAAN TERHADAP PERTUMBUHAN AWAN CUMULONIMBUS (Cb) di BANDAR UDARA (BANDARA) SULTAN SYARIF KASIM II PEKANBARU - Damanik, Krispina Br; Fitri, Yulia; Gautami, Sanya (Sistem Informasi, 2016)
The formation of the Cumulonimbus (Cb) cloud is very important to be analyzed, because it may cause weather changes which is very dangerous for flight activities. This research will analyze the formation of the Cb at Pekanbaru. The data about air temperature and pressure taken on October â December 2012 at Sultan Syarif Kasim II Airport, Pekanbaru. The analysis about the formation of Cb needed to help the focecaster to give information or suggestion about the Cb formatting. The information showed that there is temperature and pressure changes which is inversely proporsional. When the temperature up, the pressure down. This analysis said that the Cb formation on October â December 2012, 79 % tended to be started with cumulus cloud. On October, there is temperatureascension from 07.00 am to 02.00 pm about 7,5 oC and the pressure decrease from 10.00 am to 04.00 pm is about 4,5 mb with 12,5 % Cb formation. On November, there is temperature ascension about 7,6 oC from 07.00 am to 02.00 pm. The pressure decreased about 4,6 mb at 10.00 am to 04.00 pm with 16,3 % Cb formation. On December, from 07.00 am to 02.00 pm, the temperature ascends about 7,1 oC and the pressure decreases about 4,1 mb with 11,9 % Cb formation. The analysis showed the higher temperature, the lower pressure make the Cb formation is bigger.